Efforts to Improve Critical Thinking Through the Discovery Learning Model on Benzene Material at De Britto College Senior High School - Suci Puji Setyowati (Journal of Research in Mathematics, Science, and Technology Education, 2026)
Critical thinking is one of the essential 21st-century skills that must be fostered in chemistry learning. However, observations indicate that students still struggle to connect the concept of benzene with a deep understanding, resulting in suboptimal development of critical thinking skills. This best practice aims to describe the implementation of the discovery learning model in enhancing the critical thinking skills of twelfth-grade MIPA 2 students at Kolese De Britto Senior High School, Yogyakarta, on the topic of benzene. The study was conducted with 29 male students aged 17–18 years. The discovery learning model was implemented through six instructional stages: stimulation, problem identification, data collection, data processing, verification, and generalization. The research instruments consisted of (1) a critical thinking test covering interpretation, analysis, evaluation, and inference with five essay questions; (2) a student activity observation sheet with ten engagement criteria; (3) open-ended interviews with six guiding questions to explore learning experiences; and (4) documentation in the form of field notes and students’ group work. Instrument validity was established through expert judgment, while the reliability of the test was analyzed using Cronbach’s Alpha coefficient of 0.82 (high category). The results revealed a significant improvement in students’ critical thinking skills. The average test score increased from 58.3 (pre-implementation) to 74.6 (initial cycle), and further to 86.2 (final practice). The N-gain analysis yielded 0.67, categorized as medium-to-high. Observations also indicated enhanced student participation in discussions, the ability to pose questions, and independent conclusion-making. In conclusion, this best practice demonstrates that the discovery learning model is effective in improving students’ critical thinking skills in learning benzene. The limitation of this study lies in the relatively small number of participants and the restricted context of a single school. Therefore, further research with a larger population and different chemistry topics is recommended to strengthen the generalizability of the findings.